Teachers’ perceptions about the use of digital games in the classroom - Κοκολάκης Δημήτριος; Βάσιου Αικατερίνη; Γερακοπούλου Πατρίτσια (Education Sciences, 2023)
Within the last few years digital games have been increasingly valued by the education community as a crucial tool of modern teaching. The aim of this study was to examine teachers’ perceptions regarding the implementation of digital games in teaching and the difficulties in integrating them into the classroom. Research was based on qualitative analysis and the main research tool was the semi-structured interview according the purpose and the research questions. Thematic analysis indicated teachers’ favorable attitude towards the use of digital games in teaching as well as the difficulties that aroused in integrating digital games into the learning process. The results of the present research can be used by educational institutions for a substantial integration of new technologies in teaching.